Stature estimation from dry bone and radiographic clavicular measurements in a Thai population - Pongpon T,; Karnda M,; Sukon P,; Pasuk M, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Stature is one of the main biological features which can be used to classify unidentified skeletal deceased. Also, precise population data is crucial for forensic anthropology frameworks. Nonetheless, the studies concerning this subject in Thailand are limited and regularly focus on long bones. This study attempts to establish stature estimation equations from clavicular dry bone and radiographic measurements. Both sides of the clavicular bones are separated from 25 female and 112 male deceased in an autopsy room situated in Bangkok, Thailand. Twelve variables of each side of the clavicle are measured. The study outcomes show that stature can be estimated by applying 3 variables in a stepwise regression analysis model in unidentified sex remains, with R2 = 0.49 and standard error of estimation (SEE) 5.238 cm. Moreover, the height of the sternal end of clavicle bones can be used to estimate stature in cases of fragmented clavicles recovered from crime scenes with R2 = 0.238 and SEE 6.353 cm. Maximum length shows the best correlation and model fit with stature (R = 0.562, R2 = 0.316 and SEE 6.020 cm) from radiographic measurements. Therefore, this study presents a complementary, beneficial method for forensic anthropologists to create biological profiles of unidentified skeletal remains in cases where the long bones are not obtainable. Moreover, stature estimation from radiographic measurements can be applied in cases of partial skeletonisation.